2015
DOI: 10.1016/j.ehb.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring obesity in the absence of a gold standard

Abstract: Measuring Obesity in the Absence of a Gold Standard * Reliable measures of body composition are essential in order to develop effective policies to tackle the costs of obesity. To date the lack of an acceptable gold-standard for measuring fatness has made it difficult to evaluate alternative measures of obesity. In this paper we draw on work in other areas of epidemiology and use latent class analysis to evaluate alternative measures of obesity in the absence of a gold standard. Using data from a representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 55 publications
0
30
0
2
Order By: Relevance
“…The results of this paper offer additional support for calls for social science datasets to include measurements of weight and height as well as of more direct and accurate measures of fatness (e.g. O'Neill, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…The results of this paper offer additional support for calls for social science datasets to include measurements of weight and height as well as of more direct and accurate measures of fatness (e.g. O'Neill, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…In future research, focusing on utilization counts as opposed to medical expenditures may allow us to better identify the specific treatments responsible for elevated medical care costs among youths with obesity. Fourth, BMI is an imperfect measure of fatness (Burkhauser and Cawley, 2008;O'Neill, 2015). Ideally, we would have more accurate measures of fatness such as percent body fat, but BMI is the only measure of obesity available in the MEPS.…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard in diagnosing obesity as well as the relationship between the different measures of obesity and other chronic diseases remains debatable. Studies within Mexican and Caucasians population have reported that prevalence of obesity in their study population differ depending on whether the classification was done with BMI or %BF [18, 19]. In a study among Australia women they showed that waist circumference and waist-to-hip ratio were better predictors of cardiovascular disease risk than BMI [20] whereas in a Nigerian population study, BMI in addition to both waist circumference and waist-to-hip ratio were excellent predictors of cardiovascular risk [16].…”
Section: Discussionmentioning
confidence: 99%